2020
DOI: 10.1142/s1793292020500368
|View full text |Cite
|
Sign up to set email alerts
|

Thin Film of TiO2–ZnO Binary Mixed Nanoparticles as Electron Transport Layers in Low-Temperature Processed Perovskite Solar Cells

Abstract: Organic–inorganic hybrid perovskite solar cells have become one of the highly promising candidates for photovoltaic technologies because of their low processing cost, rapid-growing power conversion efficiency and easy preparation process. Electron transfer layer (ETL) plays an important role in exciton separation and charge transport for perovskite devices. A TiO2–ZnO binary mixed nanoparticle (NP) ETL, which can be prepared in low-temperature hydrothermal method, was proposed. By analyzing the XRD and SEM, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The performance of related PSCs is shown in Table 1. Bilayer ETLs also work well, such as TiO 2 /SnO 2 [57][58][59][60][61][62][63][64][65][66], TiO 2 /ZnO [67,68], TiO 2 /WO 3 [69,70], TiO 2 /graphene [71,72], TiO 2 /fullerene [73], and TiO 2 /NiO [74].…”
Section: Electron Transport Layer (Etl)mentioning
confidence: 99%
“…The performance of related PSCs is shown in Table 1. Bilayer ETLs also work well, such as TiO 2 /SnO 2 [57][58][59][60][61][62][63][64][65][66], TiO 2 /ZnO [67,68], TiO 2 /WO 3 [69,70], TiO 2 /graphene [71,72], TiO 2 /fullerene [73], and TiO 2 /NiO [74].…”
Section: Electron Transport Layer (Etl)mentioning
confidence: 99%
“…In addition, for TiO2/ZnO hybrid nanosponges electrodeposited with a Zn(NO3)2 concentration of 30 mM, the charge transfer resistance decreases both in dark and illuminated conditions compared to TiO2 nanosponges. This decrease may happen due to the fact that TiO2/ZnO hybrid nanostructures have a greater number of defects as a consequence of the introduction of ZnO into the nanostructures, obtaining a more efficient charge separation and a greater number of charge carriers [30,33,50,52,53].…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%
“…However, the intralayer thermal stress resulting from the large difference in thermal expansion between the flexible substrates and the functional layers may induce defects in the functional layers, resulting in stress concentrations during service and leading to more rapid degradation. To date, many studies on low-temperature fabrication methods have been explored 8,9 including low-temperature hydrothermal processes, 10 ultraviolet ozone treatment, 11 and N 2 plasma treatment strategies. 12 Li et al 13 recently reported that FPSCs subjected to methylamine gas treatment exhibit outstanding flexibility and retain 94.5% of the initial PCE after 3000 bending cycles.…”
Section: Introductionmentioning
confidence: 99%